2011
DOI: 10.2337/db09-1305
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Hepatocyte Growth Factor/c-Met Signaling Enhances Pancreatic β-Cell Death and Accelerates the Onset of Diabetes

Abstract: OBJECTIVE-To determine the role of hepatocyte growth factor (HGF)/c-Met on b-cell survival in diabetogenic conditions in vivo and in response to cytokines in vitro.RESEARCH DESIGN AND METHODS-We generated pancreasspecific c-Met-null (PancMet KO) mice and characterized their response to diabetes induced by multiple low-dose streptozotocin (MLDS) administration. We also analyzed the effect of HGF/c-Met signaling in vitro on cytokine-induced b-cell death in mouse and human islets, specifically examining the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
122
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 52 publications
2
122
1
3
Order By: Relevance
“…ntu.edu.tw/) and a literature search, we identified other miRNA targets potentially explaining the functional effects observed. In hepatocytes, miR-199a-3p regulates the expression of mTOR and of the transcription factor cMET [21], two proteins known to play important roles in the control of beta cell mass and survival [22,23]. We found that upregulation of miR-199a-3p results in decreased expression of mTOR and cMET also in MIN6B1 cells (ESM Fig.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…ntu.edu.tw/) and a literature search, we identified other miRNA targets potentially explaining the functional effects observed. In hepatocytes, miR-199a-3p regulates the expression of mTOR and of the transcription factor cMET [21], two proteins known to play important roles in the control of beta cell mass and survival [22,23]. We found that upregulation of miR-199a-3p results in decreased expression of mTOR and cMET also in MIN6B1 cells (ESM Fig.…”
mentioning
confidence: 62%
“…Overexpression of miR-199a-3p resulted in a reduction of the levels of mTOR and cMET, two well-characterised targets of this miRNA [21,48]. Disruption of the signalling pathways involving these two proteins is detrimental for beta cells [23,49]. Moreover, mTOR is an important regulator of autophagy, a process thought to contribute to type 2 diabetes onset [50].…”
Section: Discussionmentioning
confidence: 99%
“…3c). The expression of HGF, proposed as a beta cell survival factor [22] and as a downstream mediator of VEGF-A in pregnancy-associated compensatory beta cell growth [11], was similar in islets isolated from RIP rtTA TetO VEGF-A mice treated with DOX and those not treated (ESM Fig. 3d).…”
Section: Resultsmentioning
confidence: 90%
“…One potential endothelial cell-derived factor is HGF, which acts downstream of VEGF in hepatocyte proliferation and protection against a hepatotoxin [20] as well as during beta cell mass expansion during pregnancy [11]. In addition, HGF/c-Met signalling appears to be crucial for beta cell survival under diabetogenic conditions [22]. Nevertheless, we could not detect changes in Hgf gene expression in mice overexpressing VEGF-A, nor did HGF promote beta cell survival or protection in vitro, thereby precluding a major role for HGF in the current model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mice exhibited reduced glucose tolerance and reduced plasma insulin levels following glucose challenge; thus, the HGF-Met signaling pathway may be essential for normal glucose-dependent insulin secretion. In addition, cKO mice displayed markedly increased apoptosis and decreased proliferation following multiple low-dose streptozotocin treatments, and markedly reduced β-cell regeneration following pancreatectomy (54,55).…”
Section: Neuron-specific Metmentioning
confidence: 99%